2016
DOI: 10.2298/ciceq150122032l
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of thin layer drying of pear

Abstract: In this study, a thin - layer drying of pear slices as a function of drying conditions were examined. The experimental data set of thin - layer drying kinetics at five drying air temperatures 30, 40, 50, 60 and 70?C, and three drying air velocities 1, 1.5 and 2 m s-1 were obtained on the experimental setup, designed to imitate industrial convective dryer. Five well known thin - layer drying models from scientific literature were used to approximate the experimental data in terms of moisture r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…According to the Food and Agriculture Organization data [FAO, 2018], the worldwide pear production in 2014 was estimated at approximately 25.8 million tons. Fully mature pears play an important role in the human diet and nutrition as sources of dietary fi ber, vitamins C and B 6 , and minerals such as magnesium and potassium [Lutovska et al, 2016]. They are eaten in both the natural and processed forms as purees, jams, and dried pears [Santos, et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Food and Agriculture Organization data [FAO, 2018], the worldwide pear production in 2014 was estimated at approximately 25.8 million tons. Fully mature pears play an important role in the human diet and nutrition as sources of dietary fi ber, vitamins C and B 6 , and minerals such as magnesium and potassium [Lutovska et al, 2016]. They are eaten in both the natural and processed forms as purees, jams, and dried pears [Santos, et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…There are ample literature data on the drying of pears using various drying methods, such as osmotic pre-treated convective air drying [González-Martínez et al, 2006], solar drying [Guiné et al, 2007], sun drying [Ferreira et al, 2008], hot air drying [Doymaz & İsmail, 2012], ultrasound-assisted infrared drying [Dujmić et al, 2013], solar stove of greenhouse type drying [Guiné et al, 2013], convective drying [Lutovska et al, 2016;Santos et al, 2014], osmo-vacuum drying [Amiripour et al, 2015], forced air convection drying [Dotto et al, 2017], microwave drying [Kuş, 2016], intermittent convective drying [Silva et al, 2014], and infrared and freeze drying [Antal et al, 2017]. To the best of our knowledge, no study has been reported on the intermittent microwave-vacuum drying effect on pear slices.…”
Section: Introductionmentioning
confidence: 99%
“…From the diagrams, it can be noticed that an increase in air drying temperature resulted in decreased values of equilibrium moisture content for a constant value of water activity (Lutovska et al, 2016a). For values of water activity over 0.85 for pear, and over 0.80 for quince, the isotherm curves intersect each other (Mitrevski et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…According to previous statistical analyzes, the best model describing the thin-layer drying characteristics of pear or quince slices has to be selected on the basis of a higher value of the performance index φ and a lower χ 2 value (Mitrevski et al, 2013). According to the results obtained from previous statistical analyzes, it was concluded that the Midilli model can be used successfully for predicting the moisture of pear slices (Lutovska et al, 2016), whereas the Hii model can be used successfully for predicting the moisture of quince slices , at any time of the drying process between drying air temperatures of 30 and 70 o C and drying air velocities of 1 to 2 ms -1 .…”
Section: Mathematial Modelling Of the Drying Curvesmentioning
confidence: 97%